Thinking in English as a strategy in creating better performance for the students' critical speaking skill - Wiwi Setia Wati; Muhammad Zuhri Dj.; Uswatun Hasanah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
The purpose of this study was to determine students’ perception regarding thinking in English as a strategy for creating a better performance for the students’ critical speaking skills. This study used qualitative research and employed observation and interviews to acquire data. Based on the observations, the researchers determined that students in English-speaking courses confront a problem: they still lack self-confidence due to variables such as a lack of vocabulary and a fear of making errors while speaking. Besides, the result of the student’s interview, all of the students gave their positive perceptions about thinking in English. One of the students argued that thinking in English was something important for him as an English learner and it could help him in practicing his speaking skill. Therefore, the researcher thought it was something appropriate to introduce thinking in English as one strategy for the students and as one option to create a better performance for the students' critical speaking skills.